2
$\begingroup$

$X$ is a stochastic variable. We have $E(X) = \mu$ and $Var(X) = \sigma^2$

Then $E(X^2) = \mu^2 + \sigma^2$

We have data $X_1, X_2, X_3 , \ldots, X_n$ from that distribution.

Then we have: $$\sum_{i=1}^n (X_i - \bar{X})^2 = \sum_{i=1}^n X_i^2-n\left( \bar{X}\right)^2$$

And we have: $$E[\sum_{i=1}^n X_i^2]= \sum_{i=1}^n E[X_i^2]$$

But why is this equation below true?

$$\sum_{i=1}^n E(X_i^2)=\sum_{i=1}^n E(X^2)$$

What is the proof of that?

$\endgroup$
  • $\begingroup$ @KitterCatter No, it's correct. Here, $\bar{X}$ is the sample mean $\bar{X} = \sum_i X_i / n$. $\endgroup$ – JiK May 17 '19 at 9:23
3
$\begingroup$

This is due to the line,

We have data $X_1, X_2, \ldots, X_n$ from that distribution.

Hence, $X_1^2, \ldots, X_n^2$ must share the same distribution and hence the same expectation too.

An alternative view can also be $X_1, \ldots , X_n$ has the same variance and expectation. Since $E[X^2]=Var(X)+(E(X))^2$, they must share the same expectation when they are squared too.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.